The adventure of education : process philosophers on learning, teaching, and research - Scarfe, Adam C. (Value Inquiry Book Series, 2009)
This book on process-relational philosophy of education suggests that the notion of Adventure is foundational for the advancement of knowledge. Learning, teaching, and research are best conceived as rhythmic and relational processes, involving curiosity, imagination, valuation, creativity, and self-realization. Thus construed, contemporary educational practices can be revitalized from pedagogies of information retention and the current overemphasis on analytic precision.